Continuous Electrical Conductivity Variation in M3(Hexaiminotriphenylene)2 (M = Co, Ni, Cu) MOF Alloys - Chen, Tianyang; Dou, Jin-Hu; Yang, Luming; Sun, Chenyue; Libretto, Nicole J; Skorupskii, Grigorii; Miller, Jeffrey T; Dincă, Mircea (Journal of the American Chemical Society, 2020)
We report on the continuous fine-scale tuning of band gaps over 0.4 eV and of the electrical conductivity of over 4 orders of magnitude in a series of highly crystalline binary alloys of two-dimensional electrically conducting metal-organic frameworks M3(HITP)2 (M = Co, Ni, Cu; HITP = 2,3,6,7,10,11-hexaiminotriphenylene). The isostructurality in the M3(HITP)2 series permits the direct synthesis of binary alloys (MxM'3-x)(HITP)2 (MM' = CuNi, CoNi, and CoCu) with metal compositions precisely controlled by precursor ratios. We attribute the continuous tuning of both band gaps and electrical conductivity to changes in free-carrier concentrations and to subtle differences in the interlayer displacement or spacing, both of which are defined by metal substitution. The activation energy of (CoxNi3-x)(HITP)2 alloys scales inversely with an increasing Ni percentage, confirming thermally activated bulk transport.We report on the continuous fine-scale tuning of band gaps over 0.4 eV and of the electrical conductivity of over 4 orders of magnitude in a series of highly crystalline binary alloys of two-dimensional electrically conducting metal-organic frameworks M3(HITP)2 (M = Co, Ni, Cu; HITP = 2,3,6,7,10,11-hexaiminotriphenylene). The isostructurality in the M3(HITP)2 series permits the direct synthesis of binary alloys (MxM'3-x)(HITP)2 (MM' = CuNi, CoNi, and CoCu) with metal compositions precisely controlled by precursor ratios. We attribute the continuous tuning of both band gaps and electrical conductivity to changes in free-carrier concentrations and to subtle differences in the interlayer displacement or spacing, both of which are defined by metal substitution. The activation energy of (CoxNi3-x)(HITP)2 alloys scales inversely with an increasing Ni percentage, confirming thermally activated bulk transport.